Unilateral percutaneous vertebroplasty for symptomatic osteoporotic vertebral compression fractures -evaluation of radiological and clinical outcomes - Pooswamy, Shanmuga Sundaram; Muralidharagopalan, Niranjanan Raghavn (International Journal of Research in Orthopaedics, 2018)
Background: Vertebral fractures are the most common type of osteoporotic fractures. These are developing into a significant health problem worldwide as about 30% of the patients above 50 years suffer from a fracture secondary to osteoporosis. Osteoporotic vertebral fractures may be treated with rest and analgesics. Some fractures may also require surgery. Percutaneous procedure like vertebroplasty and kyphoplasty done under local anaesthesia can reduce the pain and restore height of vertebral body without need for an open surgery. The aim of the study was to assess the clinical and radiological outcomes following unilateral percutaneous vertebroplasty under local anaesthesia. Methods: 21 patients who underwent unilateral vertebroplasty for symptomatic osteoporotic compression fracture between 2012 and 2015 were included in the study. Unilateral vertebroplasty using an 11-gauge trocar through transpedicular technique was performed under c-arm guidance. Patient was mobilized as soon as tolerated. Oswestry disability index and visual analogue scale were assessed pre-operatively, in the immediate post-op and at 1-year follow up. Results: There were 15 females and 6 males. The mean age was 70.04±6.07 years. The pre-op ODI score was 76.8±7.6. The pre-op VAS score was 7.66±0.71. The average time period from fracture to vertebroplasty is 4.19±3.19 days. The immediate post-operative VAS score was 5.76±0.8 and the ODI score was 62.85±7.17. The VAS at final follow up was 1.23±1.19. ODI at final follow up was 9.04±3.19. There was a showed a significant improvement when preoperative, immediate post-operative ODI and VAS scores and final follow up (p<0.001). Conclusions: In our study unilateral percutaneous vertebroplasty has provided pain relief, early mobilization of the patient with less complication without the requirement of general anaesthesia.